Peran Pendidikan Dan Pelatihan (DIKLAT) Dalam Meningkatkan Kinerja Pegawai Di Kabupaten Probolinggo - Mastina Maksin; Syarla Fian Fitria Rasyida; M. Rizky Hidayatullah; Siti Nur Fadhilah (Populer: Jurnal Penelitian Mahasiswa, 2024)
Education and Training (DIKLAT) plays a vital role in developing individuals, especially in terms of improving employee performance. Studies have shown that TRAINING plays an important role in increasing employee performance. The aim of this research is to analyze the importance of the role of education and training in improving employee performance in Probolinggo district. This research uses a qualitative approach method where the data comes from observations and reading sources related to education and training. This research shows that education and training has various benefits, benefits for employees who carry out education and training, they can gain additional knowledge and improve their skills, and benefits for organizations that carry out education and training activities can get employees who are stratified, so that it has a good impact in the future progress of the organization..